HUBUNGAN PENGETAHUAN DAN PENCEGAHAN DENGAN KEJADIAN VARISES TUNGKAI BAWAH PADA PERAWAT PEREMPUAN DI RS CAMATHA SAHIDYA KOTA BATAM - Sukma Sahreni; Yani Christina (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Varicose veins of the lower limbs are diseases that are related to a person's life habits. This disease still received little attention, because this disorder is considered mild and a low mortality rate. However, varicose veins have several risky complications and are rarely noticed such as chronic venous insufficiency that will cause edema. From the above reasons, researchers are interested in examining the relationship of knowledge and prevention with the incidence of varicose veins in female nurses at Camatha Sahidya Hospital, Batam City in 2018. This research is a quantitative type with a descriptive-analytic research design with a cross-sectional approach conducted in November 2018. The total sample in Camatha Sahidya Hospital is 81 people. This study uses an Accidental Sampling of data collection techniques. Data were analyzed univariately and bivariate by computer using the chi-square statistical test. Based on statistical test results, it was found that there was no significant relationship between knowledge and the incidence of varicose lower limbs in female nurses at Camatha Sahidya Hospital with p-value = 0.177. , 8%), the category of good knowledge and the incidence of positive varicose veins were 25 nurses (53.2%), the category of bad knowledge and the incidence of varicose veins were positive there were 24 nurses (70.6%), the category of bad knowledge and the incidence of varicose veins were negative there were 10 nurses ( 29.4%) Then there was also a significant relationship between the level of prevention with the incidence of varicose veins in female nurses at Camatha Sahidya Hospital with p-value = 0.012. ), good prevention categories with the incidence of positive varicose veins were 35 nurses (72.9%), prevention categories b However, with the incidence of positive varicose veins there were 14 nurses (42.4%), the category of poor prevention with the incidence of negative varicose veins was 19 nurses (57.6%). From the results of the study it was concluded that there was no significant relationship between knowledge and the incidence of varicose lower limbs and there was a significant relationship between the prevention and incidence of varicose lower limbs in female nurses at Camatha Sahidya Hospital in 2018.